Sistem Payroll dalam Pengumpulan Zakat Profesi Aparatur Sipil Negara: Kajian Hukum Islam dan Kebijakan Daerah - Ma'rur, Muhammad (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2025)
Background. Professional zakat represents an adaptation of classical zakat jurisprudence to the realities of the modern economy, particularly for civil servants (ASN) who receive regular salaries. The Indonesian government has implemented an automatic salary deduction (payroll system) to facilitate zakat collection through BAZNAS and UPZ. However, this policy raises questions of shar‘ī validity, especially regarding the fulfillment of nisab requirements and the intention (niyyah) of the zakat payer (muzakki).Aim. This study aims to analyze the conformity of the payroll zakat system for civil servants with Islamic legal principles and its alignment with regional zakat regulations in Indonesia.Methods. The research employs a qualitative library research approach using content analysis of classical and contemporary fiqh literature, statutory laws, and regional regulations concerning professional zakat.Results. The findings indicate that the payroll system effectively enhances participation and transparency in zakat collection through official institutions such as BAZNAS and UPZ. Nevertheless, from a fiqh perspective, uniform deductions without verifying the nisab threshold—set at the equivalent of 85 grams of gold or approximately IDR 85,685,972 per year—raise issues of zakat validity. Zakat is obligatory only for those whose income meets or exceeds this threshold after essential needs are deducted; otherwise, deductions should be classified as voluntary shadaqah tathawwu‘iyyah. Therefore, harmonization between regional regulations, MUI fatwas, and BAZNAS guidelines is essential to ensure that the payroll zakat system is not only administratively efficient but also valid and just according to Islamic law.